Single-cell sequencing uncovers a high ESM1-expression endothelial cell subpopulation associated with bladder cancer progression and the immunosuppressive microenvironment - Yifeng Qiu; Yuhan Wang; Jiahe Liu; Baohua Liu; Kai Sun; Qi Hou (Scientific Reports)
Abstract Despite remarkable advancements in therapeutic strategies, a considerable proportion of patients with bladder cancer (BC) still experience disease progression and unfavorable prognosis. The heterogeneity and biological functions of tumor endothelial cells (ECs) during BC progression remain poorly understood. We collected scRNA-seq data from BC samples and identified two EC subpopulations through hierarchical clustering analysis. The activity of signaling pathways in distinct EC subpopulations was assessed utilizing AUCell analysis. Gene regulatory networks (GRN) were constructed and analyzed for different EC subpopulations using the pySCENIC algorithm. Additionally, we investigated the association between the abundance of EC subpopulations and both clinical prognosis and immune cell infiltration. The biological effects of ESM1 protein on BC cells were further validated through EdU and Transwell assays. We analyzed 7,519 CD45-negative single cells from BC tissues and discerned two distinct EC subpopulations. The two subpopulations were characterized by high expression of ESM1 (S1 ECs) and CXCL2 (S2 ECs), respectively. In S1 ECs, we observed significant activation of signaling pathways involved in tumor promotion, including angiogenesis and cell proliferation. Additionally, our GRN analysis uncovered notable differences in transcription factor activity between S1 and S2 ECs. Moreover, ESM1 protein promoted proliferation and migration of BC cells. Patients with higher abundance of the S1 EC subpopulation exhibited more unfavorable clinical outcomes and increased infiltration of inhibitory immune cells. Our findings elucidate the transcriptional profiles and biological roles of the high ESM1-expression endothelial cell subpopulation in BC. This subpopulation is associated with poor prognosis and immunosuppressive tumor microenvironment. Accordingly, targeting endothelial cells with high ESM1 expression may offer a novel therapeutic strategy for patients with BC.